Patterns in the sand: A pleistocene hominin signature along the South African coastline?. Issue 6 (December 2019) - Helm, Charles William; Cawthra, Hayley C.; De Vynck, Jan C.; Helm, Carina J.; Rust, Renee; Stear, Willo
Abstract: The Cape south coast of South Africa boasts one of the richest Middle Stone Age (MSA) archaeological records in the world. Here coastal caves and rock shelters contain well-documented archives of early humans, including early evidence of human adornment and jewelry, rock engraving and rock paSabstextinting. It has been suggested that palaeoenvironmental conditions in the area were critical to the survival of the human species. Humans travelled over dune surfaces, interdune areas and beaches during this period. These are now preserved as palaeosurfaces in aeolianites and cemented foreshore deposits, through which the ancient landscapes can be interpreted. Such contemporary sand surfaces may have formed potential canvases on which foraging behaviour or the creation of patterns or symbols could have been recorded. We question whether MSA humans left evidence of their presence other than their footprints when moving over these surfaces, and if so, whether such evidence can be discerned and interpreted today, as a hominin signature preserved in exposures of aeolianite and cemented foreshore deposits. We discuss other agents that could have caused similar patterns, and we consider the merits of eight sites that we have identified on the Cape south coast. In combination they encapsulate the complexity, challenges and potential of such study. We conclude that evidence at some of these sites suggests an anthropic origin, potentially constituting a previously undocumented form of MSA hominin expression and activity.